Elementary School Students’ Experience on WhatsApp Cyberbullying: Victimization through Social Networking Sites in Classmates - Hidayah, Ratna; Sugito (International Journal of Psychosocial Rehabilitation, 2020)
The fast growing of technology affects many aspects of human life. Huge shifting of any social interactions and phenomenon occurred as the result of technology to make them be borderless. Bullying in the context of public has shifted into the cyber form through some social networking platforms available, such as; WhatsApp. Students’ experience on cyberbullying as part of victimization is seen to be more vulnerable phenomenon. The purpose of this research is to examine students’ experience in cyberbullying by means of WhatsApp group within the classmates across gender and grades. This research involved 3 elementary schools students by fourth to sixth grade ranging from nine to twelve years old. A questionnaire dealing with the victimization through cyberbullying in WhatsApp classmates group had been completed by them to gain the data as the private discourse. It was assessed by considering the types of cyberbullying consisted of; visual bullying, verbal bullying and exclusion. The results showed that cyberbullying by social networking site as in WhatsApp as occurred in the classmates group is more vulnerable compared to direct public victimization in all level of grades. It was also found that gender has not contributed to any differences on the behavior in cyberbullying.